The influence of pharmacist-led collaborative care on clinical outcomes in type 2 diabetes mellitus: a multicenter randomized control trial - Iqbal, Muhammad Zahid; Alqahtani, Saad Saeed; Mubarak, Naeem; Shahid, Sara; Mohammed, Rafiuddin; Mustafa, Abid; Khan, Amer Hayat; Iqbal, Muhammad Shahid (Frontiers in Public Health, 2024)
Background: Health care providers are mandated to deliver specialized care for the treatment and control of type 2 diabetes mellitus. In Malaysia, Diabetes Medication Therapy Adherence Clinics (DMTAC) within tertiary hospitals have designated pharmacists to administer these services.Objective: To assess the effects of pharmacist-led interventions within Diabetes Medication Therapy Adherence Clinics (DMTAC) on outcomes for patients with type 2 diabetes mellitus in two distinct hospitals in Kedah, Malaysia.Methods: Patients with type 2 diabetes were randomly selected from the two hospitals included in this study. The study population was divided into two equal groups. The control group comprised of 200 patients receiving routine treatment from the hospitals. On the contrary, intervention group included those patients with type 2 diabetes (200), who were receiving separate counselling sessions from pharmacists of DMTAC departments along with the usual treatment. The study spanned a duration of one year, during which both study groups participated in two distinct visits.Results: Parametric data was analyzed through paired t-test and one-way ANOVA, whereas nonparametric data was analyzed by Chi-square test through SPSS v24. P < 0.05 was considered statistically significant. The study presented the results of greater reduction in HBA1c level in intervention group as compared to the control group (3.59% & 2.17%) (p < 0.001). Moreover, Systolic and Diastolic values of BP in interventional group was significantly reduced as well i.e., 9.29mmHg/ 7.58mmHg (p<0.005). Furthermore, cholesterol level was also significantly improved in interventional group patients i.e., (0.87mmol/L) (p<0.001).Based on the findings of the current study it has been proven that involving pharmacists leads to improved control of diabetes mellitus. Therefore, it is recommended that the government initiate Diabetes Medication Therapy Adherence Clinic (DMTAC) services in both private and government hospitals and clinics throughout Malaysia. Furthermore, future studies should assess the impact of pharmacist interventions on other chronic conditions, including but not limited to asthma, arthritis, cancer, Alzheimer's disease, and dementia.